Structural Characteristics, Stability, and Anticoagulant Activity of Bombyx mori Chitosan Sulfate - Rakhmanova, V.N.; Yugay, S.M.; Milusheva, R.Yu.; Shakhabutdinov, S.Sh.; Ashurov, N.Sh.; Gulomjonov, Kh.A.; Atakhanov, A.A.; Rashidova, S.Sh. (Karaganda National Research University named after academician Ye.A. Buketov, 2026)
Chitosan sulfate (CS) is a promising polyelectrolyte for biomedical applications due to its anticoagulant properties. However, the relationship between the synthesis conditions of CS derived from Bombyx mori silkworm chitosan, its structural characteristics, and its biological activity remains insufficiently studied. CS samples with varying degrees of substitution (DS) were synthesized via sulfation with chlorosulfonic acid at different temperatures (50, 60, and 80 °C). The structure was characterized using FTIR spectroscopy and X-ray diffraction analysis. The physicochemical properties were evaluated through water vapor sorption, rheology, and solution stability tests conducted over 30 days. The anticoagulant activity of CS was assessed in vivo using a rabbit model of hypercholesterolemia. Successful sulfation resulted in DS values ranging from 0.96 to 1.21, leading to significant amorphization of the polymer structure. All CS samples exhibited high hydrophilicity with sigmoid-shaped sorption isotherms and demonstrated typical polyelectrolyte rheological behavior. Aqueous solutions of CS remained stable throughout the observation period. Importantly, the CS sample with the highest DS (1.21) showed the most pronounced anticoagulant effect, reducing platelet aggregation by 20 % compared with the heparin control group. The sulfation temperature is a key parameter determining the DS and, consequently, the properties of Bombyx mori chitosan sulfate. The derivative with DS = 1.21 demonstrates anticoagulant activity comparable to heparin, highlighting its potential as a bioactive material. Further research should focus on elucidating the precise molecular mechanisms of its anticoagulant action and evaluating its long-term biocompatibility and efficacy in vivo.
Keywords: chitosan sulfate; Bombyx mori; degree of substitution; IR spectroscopy; X-ray structural analysis; water sorption; rheology; anticoagulant activity